Increased Heart Rate Variability following Elective Percutaneous Coronary Intervention in Patients with Stable Coronary Artery Disease and Preprocedural Anxiety. (20th December 2019) - Oktaramdani, Tessa; Mudjaddid, E.; Muhadi,; Shatri, Hamzah
Abstract : Background . There is a strong association between chronic ischemia and autonomic imbalance. Percutaneous coronary intervention (PCI) may restore autonomic balance in patients with stable coronary artery disease (SCAD), which is characterized by increased heart rate variability (HRV). Anxiety is often found in patients who are going to undergo invasive procedures and has been identified to induce autonomic imbalance. The aim of our study is to identify the impact of preprocedural anxiety on increased HRV following an elective PCI. Methods . Our study was a pretest and post-test correlation study involving 44 SCAD patients who underwent elective PCI at Cipto Mangunkusumo National Hospital. The HRV was measured before and after PCI. Anxiety symptoms were evaluated using Hospital Anxiety Depression Score (HADS) questionnaires. Results . We found a higher increase on HRV parameter following the PCI of subjects in the nonanxiety group compared with the anxiety group (median = 9.11 vs. 2.83; U = 154.00; p = 0.043 ). Conclusions . Preprocedural anxiety may inhibit HRV increase following PCI procedure.